The effect of ivabradine therapy on dilated cardiomyopathy patients with congestive heart failure: a systematic review and meta-analysis - Yang, Juntao; Lv, Tingting; Zhou, Jiedong; Lin, Hui; Zhao, Bingjie; Lou, Haifei; Liu, Hanxuan; Zhang, Tao; Guo, Hangyuan; Chi, Jufang (Frontiers in Cardiovascular Medicine, 2023)
Background: Ivabradine improves cardiac function in patients with heart failure, but its effect on dilated cardiomyopathy (DCM) remains unclear. We performed a systematic review and meta-analysis to study the efficacy and potential mechanisms of ivabradine's effect on cardiac function and prognosis in patients with DCM.Methods: We searched PubMed, Cochrane Library, Embase, Web of Science, and four registers through September 28, 2022. All controlled trials of ivabradine for the treatment of DCM with congestive heart failure were included. Articles were limited to English, with the full text and necessary data available. We performed random-or fixed effects meta-analyses for all included outcome measures and compared the effect sizes for outcomes in patients treated with and without ivabradine. The quality of the studies was assessed using the Cochrane risk-of-bias tool for randomized trials (RoB2.0).Five trials with 357 participants were included. The pooled risk ratio was 0.48 (95% confidence interval [CI] [0.18, 1.25]) for all-cause mortality and 0.38 (95% CI [0.12, 1.23]) for cardiac mortality. The pooled mean difference was -15.95 (95% CI [-19.97, -11.92]) for resting heart rate, 3.96 (95%CI [0.99, 6.93]) for systolic blood pressure, 2.93 (95% CI [2.09, 3.77]) for left ventricular ejection fraction, -5.90 (95% CI [-9.36, -2.44]) for left ventricular end-systolic diameter, -3.41 (95% CI [-5.24, -1.58]) for left ventricular end-diastolic diameter, -0.81 (95% CI [-1.00, -0.62]) for left ventricular end-systolic volume, -0.67 (95% CI [-0.86, -0.48]) for left ventricular enddiastolic volume, -11.01 (95% CI [-19.66, -2.35]) for Minnesota Living with Heart Failure score, and -0.52 (95% CI [-0.73, -0.31]) for New York Heart Association class.Interpretation: Ivabradine reduces heart rate and ventricular volume, and improves cardiac function in patients with DCM, but showed no significant effect on the prognosis of patients.